Student-led microfluidics lab practicals: Improving engagement and learning outcomes - Morton, J. A. S. (Biomicrofluidics, 2016)
Microfluidics has shown rapid growth in both research and development and offers significant commercialisation potential for biomedical and diagnostic applications in particular. However, there is a lack of awareness of microfluidics outside the field of study, and few dedicated educational programmes are available. While many topics incorporate microfluidics teaching, reported initiatives in the literature have not yet taken a problem based learning (PBL) approach to the delivery of practical sessions. The educational approaches already reported typically focus upon production and testing of pre-determined device designs for specific applications, using a “recipe” style of lab teaching. Here, we report on a newly designed lab section of a microfluidic teaching component utilising problem based learning (PBL) to involve the students in all aspects of design, manufacture, and performance characterisation of microfluidic solutions. Details of the lab design and development are given enabling others to replicate the lab structure described here or use it as a basis for the design of similar PBL microfluidics teaching labs. A key focus of the work has been the evaluation of the student experience, and the results of a survey indicate a high degree of student satisfaction and skills development due to the PBL approach.